2009
DOI: 10.4170/jaem.2009.46330
|View full text |Cite
|
Sign up to set email alerts
|

Acil Servise Başvuran Akut İskemik İnmeli 124 Hastanın Geriye Yönelik Bir Yıllık İncelenmesi

Abstract: AIM:We aimed to intend to contribute to our countries database for acute stroke patients with identifying etiological, epidemiological, demographic and clinical features of those patients. METHODS:This is a retrospective descriptive study. Patients' charts are identified with help of ICD-10 coding system. 124 patients were enrolled to the study. RESULTS:Patients in male gender were 56.5 % (n: 70) and mean age of the study group was 67.5 ± 11.8. Average time of the onset of the symptoms was found to be 13.0 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 16 publications
3
9
0
18
Order By: Relevance
“…Of the studies made with different age groups which suffer from stroke, the rate was found higher between the ages of 60-70 [13,14]. In the study by Kıyan et al [15], the incidence of stroke below the age of 45 was found 5 % and it was found 6,1 % in the study by Şahin et al [16]. In our study, compatible with the literature, the rate of stroke increases with age.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Of the studies made with different age groups which suffer from stroke, the rate was found higher between the ages of 60-70 [13,14]. In the study by Kıyan et al [15], the incidence of stroke below the age of 45 was found 5 % and it was found 6,1 % in the study by Şahin et al [16]. In our study, compatible with the literature, the rate of stroke increases with age.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in the studies made in the Middle East and Asian countries [28][29][30]. There are also studies showing that the patients already have hypertensive findings at the time of applying to the emergency service among the researches related to tension values of the patients with stroke [14,15,23]. In the study by Efstathiou et al [25], it was found that the mean of systolic blood pressure (SBP) in the patients with ischemic stroke was 161,7±21,5 mmHg and 165,4±15,3 mmHg for the patients with hemorrhagic stroke.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Kıyan et al studied 124 stroke patients and observed that 60.5% of them contacted emergency services during the night (18:00-08:00) (19). This may be due to an increase in CO2 levels at night, which leads to vasodilatation and causes a secondary headache to develop.…”
Section: Discussionmentioning
confidence: 99%